1997
DOI: 10.1007/s004150050155
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal calcium metabolism in myotonic dystrophy as shown by the Ellsworth-Howard test and its relation to CTG triplet repeat length

Abstract: Myotonic dystrophy (DM) is an autosomal dominant disorder characterized by peculiar clinical features. Its molecular basis is the unstable expansion of a CTG triplet repeat in the gene encoding myotonin protein kinase (Mt-PK), the nucleotide sequence of which has extensive homology to the cyclic AMP (cAMP)-dependent protein kinase gene. Extensive efforts have been made to clarify the signal transduction pathway in which the responsible gene operates, but confirming evidence has yet to be obtained. Because some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…7 CTG repeat expansion in somatic cells of DM patients generally is considered to occur during gametogenesis or early embryonic development, but CTG repeat expansion size is reported to increase over the lifetime of DM patients, 21,24 and both disease severity and CTG repeat size may increase over the course of the illness. 13 These and our findings support the hypothesis that elongation of the CTG repeat occurs during acquired cell proliferation. This paper was presented at the American Academy of Otolaryngology-Head and Neck Surgery Annual Meeting in San Antonio, Texas, September 1998.…”
Section: Discussionsupporting
confidence: 90%
“…7 CTG repeat expansion in somatic cells of DM patients generally is considered to occur during gametogenesis or early embryonic development, but CTG repeat expansion size is reported to increase over the lifetime of DM patients, 21,24 and both disease severity and CTG repeat size may increase over the course of the illness. 13 These and our findings support the hypothesis that elongation of the CTG repeat occurs during acquired cell proliferation. This paper was presented at the American Academy of Otolaryngology-Head and Neck Surgery Annual Meeting in San Antonio, Texas, September 1998.…”
Section: Discussionsupporting
confidence: 90%
“…Several recent reports have shown that the size of the CTG triplet repeat is correlated quantitatively with such clinical indexes of DM as the phosphaturic response in the Ellsworth-Howard test [21,27], intelligence quotient [11,21,27], apnoea index [21] and cardiac functions [42]. We found a significant negative correlation between EF sizes and horizontal saccadic velocity.…”
Section: Discussionmentioning
confidence: 49%
“…A few studies have reported quantitative or semiquantitative analysis of the correlation between muscle involvement and (CTG)n length in DM1 patients [10,13,27]. Kinoshita et al [13] and Jaspert et al [10] grossly evaluated the muscle status of DM1 patients based on the muscular disability rating scale (MDRS) of Mathieu et al [17] or the muscle disability test described by Stuart et al [26] and reported a significant correlation between the extent of muscle weakness and (CTG)n length.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that the severity of various clinical symptoms of DM1 is closely related to (CTG)n length [2,3,13,14,22]. Findings of neuro-otological examinations, including eye movement and the SR, can contribute to a quantitative evaluation of muscle involvement in DM1.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation